PENERAPAN SANKSI PIDANA TERHADAP PERDAGANGAN TELUR PENYU BERDASARKAN UNDANG UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBER DAYA ALAM HAYATI DAN EKOSISTEMNYA DI SUMATERA BARAT - MUSTIKA, NILA; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Sea turtles are one of the rare animals that have been protected by the government, the use of unsustainable turtle resources among them in the form of poaching, collecting or harvesting less turtle eggscontrolled, and trade in turtle resources illegally, thereby reducing the turtle population in the wild. Actors trading eggs turtle, in accordance with Article 40 Paragraph (2) of Law Number 5 of 1990 concerningConservation of Natural Resources and Ecosystems, can be sentenced to prison a maximum of five years in prison and a fine of Rp. 100,000,000. Cases per turtle egg trade have been tried in Padang District Court.The purpose of this research is to find out how the application of criminal sanctions against the perpetrators of turtle egg trade by a judge in Case Number 467/Pid.Sus/2014/PN.Pdg the judge in imposing a criminal case against the perpetrator of the turtle egg trade in Case Number 467/ Pid.Sus/ 2014/PN.Pdg and Case No. 202/Pid.sus/2016/PN.Pdg. The type of research used in this study is sociological legal research. In sociological research, the method of analysis is adjusted to the categories of data and the wishes of researchers. The analysis carried out is quantitative data analysis, namely the data analyzed using statistics or mathematics or the like.The results of this study are that of the two decisions against the criminal offense handed down by the judge still below the maximum criminal sentence and the judge's verdict, which is a trial sentence against the perpetrator of a repeat of a criminal offense. In imposing a criminal, judge referring to juridical considerations namely, the Public Prosecutor's Indictment, statement of the defendant, witness testimony, expert testimony, evidence and non-juridical considerations namely, things that are burdensome and mitigating.